Pesquisa das deleções -a3.7 e -a4.2 no agrupamento de genes da alfa-globina humana e avaliação de perfil clínico-laboratorial em pacientes com fenótipo de hemoglobina AS - Nogueira, Tatiana Lúcia Santos (2009)
﻿Interactions between thalassemic genes and Hb S have been reported, and may produce great diversity of symptoms, with important variations which cause since fetal death to asymptomatic situations. Individuals with sickle cell trait are considered asymptomatic carriers of Hb S, however, there are reports of important clinical signs and symptoms, including sudden death. The aim of this study was to evaluate individuals with hemoglobin AS phenotype, find the interaction of alpha thalassemia with sickle cell trait in this population and to verify possible interactions clinical-laboratory. 61 individuals were selected in accordance with hemoglobin AA phenotype (n = 31) and AS (n = 30). All of them were submitted to molecular analysis for the a3.7 and a4.2 deletions and analysis of hematologic, biochemical and urinary profiles. In the evaluation of hematological parameters, the MCV medium (79.85 fL ± 3.2) was significantly lower (p < 0.0001) than the AS individuals with alpha thalassemia. Individuals with AS phenotype and alpha thalassemia showed S hemoglobin significantly smaller in relation to individuals who inherited only to the variant S. Regarding biochemical parameters, the medium concentration serum iron in individuals with AA phenotype (77 mcg/dL ± 30) was significantly lower (p = 0.013) than in AS individuals (98 mcg/dL ± 34) however, both groups remained within normal limits of reference. The other biochemical parameters analyzed, ferritin, transferrin, total iron binding capacity, total bilirrubin and fractions and lactate dehydrogenase revealed no relevant differences. In the analysis of urinary profile, was not observed statistical difference (p = 1.000) between the groups regarding the presence of hemoglobinury and hematury. The alpha thalassemia frequency in the studied population was 25.0%. In individuals with hemoglobin AS, 13.3% presented interaction with alpha -thalassemia ( a 3.7/aa). Among individuals with normal hemoglobin phenotype, five (8.3%) were heterozygotes for the a3.7 deletion and one (1.7%) was heterozygous for a4.2 deletion. One (1.7%) individual was detected like carrier of variant hemoglobin alpha chain not identified in association with the alpha thalassemia ( a3.7/aa). The osmotic fragility test with sodium chloride to 0.36% and the microscopic visualization of intra-erythrocyte hemoglobin H inclusions with brilliant cresyl blue were not effective methodologies in the diagnosis of alpha thalassemia. The historic of the reports of clinical follow up in outpatient clinics of different medical specialties was higher in individuals with sickle cell trait, indicating that the inheritance of hemoglobin S had influence the degree of morbidity in these individuals. The molecular diagnosis for alpha thalassemia (deletion of one gene) is of extreme importance, both for patients with sickle cell trait, as for individuals with normal hemoglobin phenotype, even in the absence of hematological parameters altered, emphasizing that the use of microcytosis and hypochromia as a diagnostic criterion for alpha thalassemia may underestimate the frequencies of this genetic modification.